PENATAAN RUANG DI PROVINSI RIAU TAHUN 2010-2015 - Harry Helmy; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Spatial is a system of spatial planning, spatial utilization and control of spaceutilization. With the expiration RTRW Riau Province in 2009 had an impact ondevelopment and has the potential to inhibit the growth of industry and the regionaleconomy. The research problem is How the arrangement of space in Riau Province inthe absence of regulation Spatial Plan (RTRW) and How the implications of spatialplanning without spatial regulation in the province of Riau. This study aims todetermine the arrangement of space in Riau Province in the absence of regulationSpatial Plan (RTRW) and to know the implications of the arrangement of space withoutspatial regulation in the province of Riau.This research method is qualitative method with the type of data used primarydata and secondary data, data sources and documents obtained through a researchinformants. Data were collected through interviews and documentation, and thenanalyzed in a descriptive way to provide an overview of the research results.The results of this research are of Spatial Planning in Riau Province Year 2010-2015 has yet to be separated into a regional regulation by the Provincial Governmentof Riau because the seat has not increased the area proposed Regional Government ofRiau Province to the Ministry of Forestry, thus implies Unable to RTRW Regency / Cityset , exemption of land, and inhibit the development and investment.Keywords: Spatial, Policy, Riau Province